Kontribusi Pembelajaran Projek Kreatif dan Kewirausahaan dalam Meningkatkan Kesiapan Berwirausaha Siswa SMK Negeri 1 Kecamatan Luak - Divani, Mardhyah; Indrayeni, Wiwik; Yulastri, Asmar; Andriani, Cici (STKIP PGRI SITUBONDO, 2024)
This research is motivated by the relatively high number of vocational school unemployment, one way to prevent and reduce it is to prepare students for entrepreneurship. Preparing students who are ready for entrepreneurship is done through learning Creative Projects and Entrepreneurship. This research aims to describe the learning outcomes for Creative Projects and Entrepreneurship, describe entrepreneurial readiness, and analyze the relationship between Creative projects and Entrepreneurship learning outcomes and students' entrepreneurial readiness at SMK Negeri 1 Luak District. This type of research is quantitative with a correlational approach. The sample for this research was 156 class XII students at SMK Negeri 1 Luak District. The sampling technique used was Proportional Random Sampling, and the data was analyzed using descriptive and correlation analysis. The research results show that the learning outcomes for Creative Projects and Entrepreneurship of class XII students are in the low category with a percentage of 33%, while students' entrepreneurial readiness is in the medium category with a percentage of 39%. Based on the hypothesis test results, it can be concluded that there is a positive and significant relationship between Creative and Entrepreneurship Project Learning Outcomes and the Entrepreneurial Readiness of class XII students at SMK Negeri 1 Luak District. So that the learning outcomes and learning can be used as a reference in increasing students' entrepreneurial readiness.